NILAI-NILAI MORAL TOKOH MARJA DALAM NOVEL MANJALI DAN CAKRABIRAWA KARYA AYU UTAMI - Rici, Rici; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
The purpose of this study is to describe the values of moral Marja character in the novel Manjali and Cakrabirawa works Ayu Utami. The values associated with: (1) conscience, (2) freedom and responsibility, (3) the rights and obligations, (4) values and norms. This research is qualitative research. The method used in this research is descriptive analysis. Results of this study are the moral values associated with Marja figures: (1) conscience can be seen from the attitude the Marja has been two-timing guilt password Yuda, (2) freedom and responsibility can be seen from the attitude of Marja in the association of free and used sleep with the ooposite sex, (3) the rights and obligations can be seen from Marja desire to learn the history of science, (4) the values and norms can be seen from the attitude Banaspatih Marja who believe the myth. Based on these results we can some suggestions as follows: (1) teachers, especially in literary appreciation that learning can moral values to students on how to behave, act, and how to interact in society, (2) the reader, can increase understanding of the literature, (3) further research, can do research on this novel with a different aspect or aspects of the same with a different novel.